Selection of Sweet Corn Inbred Lines by Agronomic Performance to Determining Hybrid Parents - Suyadi, Suyadi; Arifin, Azeri Gautama; Kurniawan, Andi (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2024)
The development of hybrid sweet corn varieties involves the selection of parental lines with specific traits to ensure good yield potential. The selection of inbred lines of sweet corn is a critical aspect of breeding programs aimed at developing improved varieties. This research will provide useful information of sweet corn inbreed lines have the potential to be developed as parent lines in the development of hybrid varieties. The study utilized 24 inbred lines (G1-G24) of sweet corn and employed a Randomized Complete Block Design (RCBD). Data analysis involved the use of analysis of variance with a 5% significance level, path and dendrogram analysis. Based on the analysis of 24 inbreed line of sweet corn, the potential for selecting parents based on quantitative traits influencing the outcome is evident in inbreed line G18, G12, G4, G23, and G20. Identification of these potential parents is essential for the genetic improvement of the population. The correlation heatmap data indicates a 41% correlation between the number of rows and cob stag length, and correlation between number of rows and ear diameter by 48%. The path diagram indicates that fresh weight, a crucial measure of crop yield, is strongly influenced by several agronomic traits, including plant height, ear length, ear diameter, dry weight, number of plants, row length, brix, and ear stalk. G24 can indeed be used as one of the parents with other group in hybrid breeding programs.